Arbuscular mycorrhizal fungi impact the production of alkannin/shikonin and their derivatives in Alkanna tinctoria Tausch. grown in semi-hydroponic and pot cultivation systems - Zhao, Yanyan; Cartabia, Annalisa; Garcés-Ruiz, Mónica; Herent, Marie-France; Quetin-Leclercq, Joëlle; Ortiz, Sergio; Declerck, Stéphane; Lalaymia, Ismahen (Frontiers in Microbiology, 2023)
Alkanna tinctoria is a medicinal plant, producing alkannin/shikonin and derivatives (A/Sd). It associates with arbuscular mycorrhizal fungi (AMF), which are known to modulate the plant secondary metabolites (SMs) biosynthesis. However, no study has compared the effects of AMF strains purchased from international collections (i.e., GINCO) with strains isolated from wild-growing A. tinctoria, on the growth and production of A/Sd in this plant. Here, three experiments were conducted. In Experiment 1, plants were associated with the GINCO strain Rhizophagus irregularis MUCL 41833 and in Experiment 2, with two strains of GINCO (R. irregularis MUCL 41833 and Rhizophagus aggregatus MUCL 49408) and two native strains (Rhizophagus irregularis and Septoglomus viscosum) in a semi-hydroponic (S-H) cultivation system. Plants were harvested after 9 and 37 days in Experiment 1 and 9 days in Experiment 2. In Experiment 3, plants were associated with the two native AMF strains and with R. irregularis MUCL 41833 and were grown for 85 days in pots under greenhouse conditions. Quantification and identification of A/Sd were performed by HPLC-PDA and by HPLC-HRMS/MS, respectively. LePGT1, LePGT2 and GHQH genes involved in the A/Sd biosynthesis were analysed through RT-qPCR. In Experiment 1, no significant differences were noticed in the production of A/Sd. Conversely, in Experiment 2 and 3, plants associated with the native AMF R. irregularis had the highest content of total A/Sd expressed as shikonin equivalent. In Experiment 1, a significantly higher relative expression of both LePGT1 and LePGT2 was observed in plants inoculated with R. irregularis MUCL 41833 compared with control plants after 37 days in the S-H cultivation system. Similarly, a significantly higher relative expression of LePGT2 in plants inoculated with R. irregularis MUCL 41833 was noticed after 9 days versus 37 days in the S-H cultivation system. In Experiment 2, a significant lower relative expression of LePGT2 was observed in native AMF R. irregularis inoculated plants compared to the control. Overall, our study showed that the native R. irregularis strain increased A/Sd production in A. tinctoria regardless of the system used, further suggesting that inoculation of native/best performing AMF is promising to improve the production of important SMs.